Are the World Junior Championship finalists for middle- and long-distance events currently competing at international level? - Pizzuto, F.; Bonato, M.; Vernillo, G.; La Torre, A.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To analyze how many finalists of the International Association of Athletics Federations (IAAF) World Junior Championships (WJCs) in the middle- and long-distance track events had dropped out from high-level competitions.